Simulação fluidodinâmica computacional para estudo do tratamento de dessulfuração do aço - Lucas Teixeira Costa (2012)
With the growing demand for high quality steels since the 80's, several secondary refining processes of steel were developed for various purposes such as decarburization, removal of inclusions, narrowing the range of chemical composition, thermal homogenization and production of steels with low level of impurity. The ultra-low sulfur steels are used in the manufacture of pipes for transporting oil and construction of offshore platform, which requires high impact strength and resistance to lamellar crack formation by interaction with hydrogen and sulfide inclusions. It is well known that the efficiency of desulfurization of the steel depends on the setting of the kinetic and thermodynamic factors that must be set simultaneously to provide theoretical and practical ways to enable the optimization of various process parameters. A model was developed allowing to simulate the process of steel desulfurization in ladle through slag-metal interaction during the injection of inert gas. This model gave important information to characterize the fluid flow condition studied, to define the velocity profiles, the steel stream velocity in the slag-metal interface, the open "eye" in the outlet of the gas and the evolution of sulfur content during the desulphurization treatment. The evolution of sulfur during treatment in steel desulphurization was accompanied in three experimental treatments that were fundamental for determining the coefficient of mass transfer. Based on this it was determinate a dimensionless correlation applicable to different operational conditions. This parameter was introduced in the mathematical model. The model was able to predict the sulfur content of steel as a function of the treatment time and was validated based on experimental data obtained in an industrial plant of steel desulphurization. After validation, the model was used to simulate various process parameters such as chemical composition of the slag, slag volume, gas flow rate and configuration of porous plug in the ladle. Finally, the developed model was applied to another industry which adopt a single porous plug in the ladle center. The model was able to correctly predict the steel desulfurization rate. Thus, it can be stated that the developed model correctly represents the steel desulfurization regardless the operating parameters.